Analysis of the Effect of Load Maneuver from Power Transformer 1 to Power Transformer 2 on Feeder Using ETAP 19.01 at PT. PLN (Persero) Idi Substation - Putri Mandasari; Badriana Badriana; Fakhruddin Akhmad Nasution (Faculty of Engineering, Malikussaleh University, 2024)
Load maneuvering on the power distribution network can have a significant impact on voltage drops along the feeder, especially in distribution substations such as PT. PLN (Persero) Idi Substation. The analysis was carried out to examine the effect of load maneuver on voltage drops in several feeders at the substation. The data used included a single line diagram, daily load patterns, feeder cable lengths and the number of feeders analyzed. Using ETAP simulation software, this study evaluates the percentage drop in voltage during load manoeuvre operations to determine its conformity to operational standards. This analysis identifies critical feeders where voltage drops exceed the allowable threshold, and provides solutions to mitigate these problems, thus ensuring stable power supply and minimizing the risk of low voltage during the load transfer process. This study analyzes the voltage drop in the electricity distribution network at PT. PLN (Persero) Idi Substation using two methods, namely manual calculation and ETAP simulation. The results of the analysis show that the value of the voltage drop percentage from the manual calculation is 1.85%, while the results of the ETAP simulation show a value of 0.013%. This significant difference shows that the method that the simulation method is more accurate in modeling the conditions of the distribution network. As an effort to mitigate voltage drops in the electricity distribution network at PT. PLN (Persero) Idi Substation, an increase in transformer capacity was carried out. The capacity of power transformer 1 is increased from 20 MVA to 25 MVA and power transformer 2 from 30 MVA to 40 MVA. In addition, the size of the cable cross-section was also increased from 240 mm to 300 mm. These results can be used as a reference in network performance evaluation and decision-making for load maneuvering to ensure a more efficient and reliable distribution of electricity. Keywords: Load maneuver, voltage drop, ETAP simulation, mitigation efforts.